2017
DOI: 10.1016/j.neubiorev.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Towards a cognitive neuroscience of self-awareness

Abstract: Self-awareness is a pivotal component of conscious experience. It is correlated with a paralimbic network of medial prefrontal/anterior cingulate and medial parietal/posterior cingulate cortical "hubs" and associated regions. Electromagnetic and transmitter manipulation have demonstrated that the network is not an epiphenomenon but instrumental in generation of self-awareness. Thus, transcranial magnetic stimulation (TMS) targeting the hubs impedes different aspects of self-awareness with a latency of 160ms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 89 publications
6
71
0
5
Order By: Relevance
“…In this regard, there is evidence that during wakefulness the right prefrontal cortex participates in self‐recognition (Keenan, Wheeler, Gallup, & Pascual‐Leone, ), metacognitive evaluation and self‐relevance (Schmitz, Kawahara‐Baccus, & Johnson, ), and in the perception of time (Koch, Oliveri, Carlesimo, & Caltagirone, ) and planning (Goel & Grafman, ). Furthermore, there is evidence that the prefrontal cortex is related to the organization of goal‐directed behavior (Fuster, ), metacognition (Middlebrooks & Sommer, ), self‐monitoring (Luu, Collins, & Tucker, ), and self‐awareness (Lou, Changeux, & Rosenstand, ). In fact, several studies have shown that alpha rhythms are modified over sensorimotor areas during the preparation, execution, and imagination of movement or during somatosensory stimulation (Arroyo et al, ; Neuper, Wörtz, & Pfurtscheller, ; Pfurtscheller, Neuper, Andrew, & Edlinger, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, there is evidence that during wakefulness the right prefrontal cortex participates in self‐recognition (Keenan, Wheeler, Gallup, & Pascual‐Leone, ), metacognitive evaluation and self‐relevance (Schmitz, Kawahara‐Baccus, & Johnson, ), and in the perception of time (Koch, Oliveri, Carlesimo, & Caltagirone, ) and planning (Goel & Grafman, ). Furthermore, there is evidence that the prefrontal cortex is related to the organization of goal‐directed behavior (Fuster, ), metacognition (Middlebrooks & Sommer, ), self‐monitoring (Luu, Collins, & Tucker, ), and self‐awareness (Lou, Changeux, & Rosenstand, ). In fact, several studies have shown that alpha rhythms are modified over sensorimotor areas during the preparation, execution, and imagination of movement or during somatosensory stimulation (Arroyo et al, ; Neuper, Wörtz, & Pfurtscheller, ; Pfurtscheller, Neuper, Andrew, & Edlinger, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether they can engage in selfreferential conscious thinking (141), and thus have self-awareness, is less certain (20,142,143). Self-awareness is viewed by many as a uniquely human experience (112,135,136,(144)(145)(146)(147). Klein (148) draws an important distinction between episodic memory (memory of what happened, where it happened, and when it happened) and autonoetic consciousness (the awareness that the facts about what, where, and when happened to you).…”
Section: A Modified Higher-order Theorymentioning
confidence: 99%
“…The cognitive functions (working memory, attention, metacognition, and so forth) and neural circuits (especially prefrontal circuits) that underlie HORs are also required for conscious experiences involving the self, including emotional states involving the self (145,(156)(157)(158)(159)(160)(161)(162) Fig. 3 for HOT).…”
Section: A Modified Higher-order Theorymentioning
confidence: 99%
“…Therefore, it is not clear that so-called subjectivity theories all endorse the claim that self-awareness properly speaking (an awareness of oneself , or a sense of self) is a necessary condition for consciousness. In any case, even outside of the debate about SCP, many publications in neuroscience, psychology and philosophy have endorsed the general idea that consciousness necessarily involves some kind of sense of self or self-awareness (e.g., Damasio, 1999; Gallagher, 2000; Gallagher and Zahavi, 2005; Strawson, 2011; Lou et al, 2016). Let us call this specific claim the “self-awareness principle” (SAP) 5 :

(SAP) Necessarily, whenever one is in a conscious state, one is minimally self-aware .

…”
Section: The Significance Of Died For Philosophy Of Mindmentioning
confidence: 99%
“…He comes close to explicitly endorsing SAP, although he does not formulate a necessity claim: “my current experience’s pre-reflective self-consciousness strikes me as egological—that is, as a form of peripheral self -awareness… There is an elusive sense of self-presence or self-manifestation inherent in even a simple conscious experience of the blue sky.” (Kriegel, 2009; p. 177). See also Damasio (1999, p. 19): “If ‘self-consciousness’ is taken to mean ‘consciousness with a sense of self’, then all human consciousness is necessarily covered by the term—there is just no other kind of consciousness as far as I can see”; and Lou et al (2016): “self-awareness is an integral function of all conscious experiences”.…”
mentioning
confidence: 99%